Financial forecasting and decision making - Davidson, Wallace N. (Wallace Norman), 1952- (American Institute of Certified Public Accountants, Inc., 2017)
Many companies fail to succeed due to poor planning, which is one reason why accountants are in big demand. Skilled at forecasting, accountants can plan a company's future by determining the maximum sustainable growth and predict its external fund requirements. This book provides you with the basic tools necessary to project the balance sheet and statements of income and cash flow, enabling you to add a unique value to your client(s) work. This book will prepare you to do the following: -Recall the basics of planning and forecasting financial statements -Recall considerations related to a basic forecasting model -Identify the evidence of growth mismanagement and develop the skills to determine maximum sustainable growth -Apply statistical procedures to forecasting -Analyze projected or forecasted financial statements.